Uterine Mass! Spectrum of Disease - Khawaja, Rehan Wazir (International Journal of Pathology, 2018)
A 45-year-old female para 4 presented in surgical OutpatientDepartment at Abbas Institute of Medical Sciences, Muzaffarabadwith history of hypogastric pain for 9 months associatedwith pervaginal bleeding and feeling of lower abdominalheaviness. She had also started noticing a masslower abdomen gradually increasing in size. The ultrasoundabdomen reported huge fibroid in the uterus. She was Hep-Cpositive with normal routine laboratory investigations. s.